Case Report on Malignant Peripheral Nerve Sheath Tumor (Journal of Pharmaceutical Negative Results, 2022)
Malignant peripheral nerve sheath tumours (MPNST) are an uncommon type of cancer that spreads from the brain stem into the body and affects the covering of the nerves. Anywhere in the body can develop MPNST, but the deep tissues of the arms, legs, and trunk are where they most frequently occur. They result in discomfort and lethargy, mostly in the affected region, and it may develop a bulge or tumour. A 22-year-old woman presented in cancer ward with the complaints of right lower limb pain with the pain score of 4/10, the intensity of pain aggravates while sitting or performing activity and relieves while at rest, also felt heaviness since 7 months. A vast blood investigation was carried out. MRI and Biopsy were done to make her diagnosis. After following investigations, she was diagnosed as a “malignant peripheral nerve sheath tumours”. Initially she was started on I.V. fluids, analgesics and injectables on the day of admission. Retroperitoneal mass excision was performed under general anaesthesia. Patient’s prognosis remains good.